The hermeneutical reading strategy in the contemporary Algerian university critical discourse,: reading in the critical work of researcher Amina Belala on the theme “The Communicative mobility in Sufi discourse (from Third century to seventh century AH)” - Boulasel, Said; Khorfi, Mohamed Salah (Journal of Human Sciences, 2021)
This scientific article addresses the problem posed by the hermeneutical reading in contemporary Algerian university critical discourse. This article will study and analyze according to the mechanisms of metacritics in particular the work of researcher Amina Belala on the theme "communicative mobility in Sufi discourse (from Third century to seventh century AH), on which we have focused our reading as a model of reading through which the researcher tried to create a critical horizon based on the question and the research by noting the textual and literary phenomena in the Sufi discourse on the one hand and by studying the functioning of the meaning of 'on the other hand without ignoring the communicative aspects which link the author of the text and the recipient reader.